Hubungan Antara Dukungan Keluarga Dengan Tingkat Stres Tahanan Di Rumah Tahanan Negara Kelas IIb Bangil - Famuji, Fathiroh Fushilah; Trigantara, Regista; Loura, Nining (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
ABSTRACT Fathiroh Fushilah Famuji, 2023.The Relationship between Family Support and the Stress Level of Prisoners in the Bangil Class IIB State Detention Center. Thesis. Bachelor of Nursing Study Program,Stikes Maharani Malang. Supervisor: (1) Ns. Regista T, M. Kep, (2)Nining Loura S, SST., M.Kes. Unpleasant conditions during the removal process are a stress trigger for residents. If left unchecked, they can trigger psychological disorders for residents. One effort in stress management is to increase social support, especially family support. The aim of this research was to determine the relationship between family support and stress levels in prisoners at the Class IIB Bangil Detention Center. The research method uses analytical observational with a cross sectional approach. The sample for this research was 70 students at the Class IIB Bangil State Detention Center. The sampling technique used was purposive sampling. The research measuring tool uses a questionnaire which is made according to family support indicators and a stress level measuring tool adopted from DASS. The research results showed that the majority of respondents had high category family support with 38 respondents (54.3%) and almost half of the respondents had normal stress levels with 29 respondents (41.4%). The results of the Pearson correlation test analysis show a significance value of 0.000 <0.05 and a Pearson correlation value of -0.839. The results of the study concluded that there was a relationship between family support and the stress level of prisoners at the Bangil Class IIB State Detention Center, showing a strong correlation and a negative relationship where the two variables had a unidirectional relationship, if family support was high then the stress level was lower. This is because nurses who have good family support can more easily develop their ability to survive and adapt to conditions that are considered difficult and which have the risk of causing stress, this is due to the high role of family members in helping to form a good sense of self-acceptance. so that it is better to feel depressed or stressed. Keywords: Family Support, Stress Level, Prisoners